Interactions between acidic proteins and crystals: stereochemical requirements in biomineralization. - Addadi, L (1985)
Acidic matrix macromolecules are intimately involved in biological crystal growth. In vitro experiments, in which crystals of calcium dicarboxylate salts were grown in the presence of aspartic acid-rich proteins, revealed a stereochemical property common to all the interacting faces. Calcite crystals are nucleated on stereochemically analogous faces when proteins are adsorbed onto a rigid substrate. The importance of this property in biomineralization is discussed.